Anti-inflammatory intestinal activity of Arctium lappa L. (Asteraceae) in TNBS colitis model - De Almeida, Ana Beatriz Albino; Sánchez-Hidalgo, Marina; Martín, Antonio Ramón; Luiz-Ferreira, Anderson; Trigo, José Roberto; Vilegas, Wagner [UNESP]; Santos, Lourdes Campaner dos [UNESP]; Souza-Brito, Alba Regina Monteiro; De La Lastra, Catalina Alarcón (Elsevier, 2013)
Ethnopharmacological relevance: In Brazilian traditional medicine, Arctium lappa (Asteraceae), has been reported to relieve gastrointestinal symptoms. Aim of the study: In the present study, we investigated the effects of the lactone sesquiterpene onopordopicrin enriched fraction (ONP fraction) from Arctium lappa in an experimental colitis model induced by 2,4,6 trinitrobenzene sulfonic acid and performed experiments to elucidate the underlying action mechanisms involved in that effect. Materials and methods: ONP fraction (25 and 50 mg/kg/day) was orally administered 48, 24 and 1 h prior to the induction of colitis and 24 h after. The inflammatory response was assessed by gross appearance, myeloperoxidase (MPO) activity, tumor necrosis factor alpha (TNF-α) levels and a histological study of the lesions. We determined cyclooxygenase (COX)-1 and -2 protein expressions by western blotting and immunohistochemistry assays. Results: TNBS group was characterized by increased colonic wall thickness, edema, diffuse inflammatory cell infiltration, increased MPO activity and TNF-α levels. On the contrary, ONP fraction (25 and 50 mg/kg) treatment significantly reduced the macroscopic inflammation scores (p<0.05 and p<0.01, respectively) and morphological alterations associated with an increase in the mucus secretion. Similarly, the degree of neutrophil infiltration and the cytokine levels were significantly ameliorated. Moreover, COX-2 expression was up regulated in TNBS-treated rats. In contrast, ONP fraction (50 mg/kg) administration reduced COX-2 overexpression. Conclusions: We have shown that the ONP fraction obtained from Arctium lappa exert marked protective effects in acute experimental colitis, confirming and justifying, at least in part, the popular use of this plant to treat gastrointestinal diseases. © 2013 Elsevier B.V. All rights reserved.
Keywords: Arctium lappa; Colitis; COX-2; Onopordopicrin; Rats; TNBS; antiinflammatory agent; cyclooxygenase 1; cyclooxygenase 2; lactone derivative; myeloperoxidase; onopordopicrin; sesquiterpene derivative; tumor necrosis factor alpha; unclassified drug; animal experiment; animal model; animal tissue; antiinflammatory activity; cell infiltration; colitis; controlled study; enzyme activity; histology; immunohistochemistry; leukocyte; male; mucus secretion; nonhuman; rat; upregulation; Western blotting; Animals; Anti-Inflammatory Agents; Arctium; Cyclooxygenase 2; Disease Models, Animal; Male; Peroxidase; Phytotherapy; Plant Extracts; Plant Leaves; Rats, Wistar; Trinitrobenzenesulfonic Acid; Tumor Necrosis Factor-alpha; Asteraceae; Rattus